Anisotropic molecular motion on cell surfaces. - Smith, B A (1979)
Photobleaching in a two-dimensional periodic pattern has been used to characterize the motion of succinylconcanavalin A receptors on the surfaces of mouse fibroblasts. These receptors were found to exhibit anisotropic two-dimensional diffusion in adherent cells having parallel stress fibers. Diffusion coefficients of the order of 10(-11) cm2/sec and 10(-12) cm2/sec were measured for diffusive motions parallel and perpendicular to these fibers. The determination of the anisotropic motion used a two-dimensional Fourier analysis. A study was made of the effect of changes in cell shape on the photobleach pattern.